Effect of pregnancy on female gait characteristics: a pilot study based on portable gait analyzer and induced acceleration analysis - Li, Xin; Lu, Zhenghui; Cen, Xuanzhen; Zhou, Yizheng; Xuan, Rongrong; Sun, Dong; Gu, Yaodong (Frontiers in Physiology, 2023)
Introduction: The changes in physical shape and center of mass during pregnancy may increase the risk of falls. However, there were few studies on the effects of maternal muscles on gait characteristics and no studies have attempted to investigate changes in induced acceleration during pregnancy. Further research in this area may help to reveal the causes of gait changes in women during pregnancy and provide ideas for the design of footwear and clothing for pregnant women. The purpose of this study is to compare gait characteristics and induced accelerations between non-pregnant and pregnant women using OpenSim musculoskeletal modeling techniques, and to analyze their impact on pregnancy gait. Methods: Forty healthy participants participated in this study, including 20 healthy non-pregnant and 20 pregnant women (32.25 ± 5.36 weeks). The portable gait analyzer was used to collect participants’ conventional gait parameters. The adjusted OpenSim personalized musculoskeletal model analyzed the participants’ kinematics, kinetics, and induced acceleration. Independent sample T-test and one-dimensional parameter statistical mapping analysis were used to compare the differences in gait characteristics between pregnant and non-pregnant women. Results: Compared to the control group, pregnancy had a 0.34 m reduction in mean walking speed (p < 0.01), a decrease in mean stride length of 0.19 m (p < 0.01), a decrease in mean stride frequency of 19.06 step/min (p < 0.01), a decrease in mean thigh acceleration of 0.14 m/s2 (p < 0.01), a decrease in mean swing work of 0.23 g (p < 0.01), and a decrease in mean leg falling strength of 0.84 g (p < 0.01). Induced acceleration analysis showed that pregnancy muscle-induced acceleration decreased in late pregnancy (p < 0.01), and the contribution of the gastrocnemius muscle to the hip and joint increased (p < 0.01). Discussion: Compared with non-pregnant women, the gait characteristics, movement amplitude, and joint moment of pregnant women changed significantly. This study observed for the first time that the pregnant women relied more on gluteus than quadriceps to extend their knee joints during walking compared with the control group. This change may be due to an adaptive change in body shape and mass during pregnancy.